Study the Effects of Vitamin D as Immune-Modulatory Agent in Type II Diabetes Mellitus Patients - Marzook, Afaf Th. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was designed to show the roles of vitamin D as immune-modulatory agent in serum type II Diabetes Mellitus Patients collected from type II Diabetes Mellitus and controls. They have been classified into two groups as the following: 1) Patients of type II DM group includes (20) individuals from both sexes with age range (35â€“65) years. 2) Control group: includes (20) healthy individuals from both sexes, with age range (30 â€“ 45) years and no previous disease which may interfere with the parameters analyzed in this research. All the blood samples were analyzed for vitamin D3, albumin, C- reactive protein (CRP), erythrocyte sedimentation rate (ESR), immunoglobulins (IgG, IgM, IgA),  Î±1- antitrypsin and total protein (TP).